Efecto del periodo crítico de competencia de malezas en el rendimiento de Caupi (vigna unguiculata l. Wajp) variedad blanco cumbaza INIA en Morales - Hermoza Bocanegra, Rubén Sixto (1998)
This study was carried out in Cumbacillo, Morales on a sandy loam soil with a crop of copwpea (Vigna unguiculata L. Walp). The crop was weeded in part and in part the weeds were allowed to grow. The objetive was to determine the critical period of competition between the weeds and cowpea crop. The experiment used 6 treatments with weeds permitted to grow and 6 treatments weeded what comprehend periods from until 10, 20, 30, 40, 50 y 60 days respectively. Two control plots were maintained during the experiment, one with weeds permitted to grow and one without weeds. Each plot had an area of 16.1 m2. The critical moment of weed competition in the case of white cowpea Cumbaza INIA was seen within the f1rat 50 days (treatment with weeds). During this period the moat severe reductions in yiel of cowpea were observed. The white cowpea Cumbaza INIA was planted September 25, 1995 and harvested November 30 and December 20 of the same year. The vegetative growth period of the cowpea was 90 days. In the economic study, treatment 1 (without weeds the entire growth period) produced the highest return with 456.00 soles/ hectare. Treatment 10 days without weeds, with weeds the entire growth period 40, 50 y 60 days with weeds economic losses with treatment 50 days with weeds reporting a loss of - S/. 441.00 soles/ha. It was also noted that an inverse relation existed between the fresh weight of weeds weight of weeds, and cowpea yield. The greater the weight of weeds the lower yield of cpwpea and viceversa